2000
DOI: 10.1114/1.1289456
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Crista Terminalis in Atrial Flutter and Fibrillation: A Computer Modeling Study

Abstract: Although atrial fibrillation is a common arrhythmia, the underlying mechanisms are incompletely understood. Recent studies have determined the role of the crista terminalis in the mechanisms of a simpler arrhythmia, atrial flutter. We hypothesize that as transverse coupling across the crista terminalis increases, the activation pattern that results is less like typical atrial flutter and more like atrial fibrillation. 6480 Van Capelle elements were coupled in an icosahedron, simulating the right atrium. Atrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…5(d)], in agreement with noncontact mapping data in humans [56]. Ellis et al reported occurrences of atrial flutter in a simplified computer model of the right atrium when transverse connections in the crista terminalis were uncoupled [42]. This observation was confirmed by Vigmond et al in a more realistic canine atrial model with reduced transverse coupling in the crista terminalis [31].…”
Section: Using Models To Study Different Mechanisms Of Arrhythmiasupporting
confidence: 53%
“…5(d)], in agreement with noncontact mapping data in humans [56]. Ellis et al reported occurrences of atrial flutter in a simplified computer model of the right atrium when transverse connections in the crista terminalis were uncoupled [42]. This observation was confirmed by Vigmond et al in a more realistic canine atrial model with reduced transverse coupling in the crista terminalis [31].…”
Section: Using Models To Study Different Mechanisms Of Arrhythmiasupporting
confidence: 53%
“…Furthermore, PMs have been found to play a role in the conversion between AF and flutter by anchoring spiral waves. 90,92 Modeling studies 43,52, 91,93 have implicated the highly anisotropic conduction and longer APD in the crista terminalis in setting up the conditions for reentry generation. Using anatomical models of the rabbit RA and of the pig RA appendage, respectively, both based on histological reconstructions, studies by Aslanidi et al 49 and Zhao et al 48 demonstrated that because electrotonic coupling transverse to fibers in the crista terminalis is weak, high-frequency pacing at the border between the crista and PMs results in a reduced safety factor, leading to unidirectional block and subsequent generation of reentry.…”
Section: Exploring Atrial Fibrillation Mechanisms: Insights From Mmentioning
confidence: 99%
“…6,9,22 Elaborate atrial models already published take into account conduction bundles and evaluate normal propagation or atrial arrhythmias with simulations lasting a few seconds. 6,9,22 For example, Harrild et al developed an anatomically accurate three-dimensional model of human atria, used for the simulation of sinus rhythm. 9 Vigmond et al developed a model of canine atria (3.3 cm wide) including Bachmann's bundle, crista terminalis and pectinate muscles.…”
Section: Biophysical Atrial Modelmentioning
confidence: 99%
“…Our single layer cell model does not include anisotropic fast-conducting regions, fiber orientation, crista terminalis and pectinate muscles, which may all play a role during AF. 6,16 A version of our model incorporating some of these aspects has been developed 3 at the expense of an increased complexity and computational load. The inclusion of such details needs further validated data.…”
Section: Limitationsmentioning
confidence: 99%